Dietary Micronutrient Intake and the Prevalence of Metabolic Conditions among Children from the United States–Affiliated Pacific Region in the Children’s Healthy Living Program - Lucia A Seale; Ashley B Yamanaka; Kristi Hammond; Eunjung Lim; Lynne R Wilkens; Pauline McFall; Tanisha F Aflague; Patricia Coleman; Travis Fleming; Leslie Shallcross; Jonathan Deenik; Rachel Novotny (Current Developments in Nutrition)
Background: Nutritional intake during childhood can shape health and well-being throughout life. Although excess macronutrient intake is considered the main driver of obesity development, micronutrients, i.e., minerals and vitamins, can potentiate or ameliorate pathological processes of adiposity. Hence, the micronutrient intake relationship to childhood obesity can guide precision approaches to nutritional needs, considering the dietary habits of a population. Childhood obesity is a health disparity throughout the United States–Affiliated Pacific (USAP) region. Objectives: The study examined the association between micronutrient intake with body mass index (BMI in kg/m2) and the presence of insulin resistance proxy, acanthosis nigricans (AN), in 3529 children aged 2–8 y from the USAP region in the Children’s Healthy Living study. Methods: The association of micronutrient intakes with BMI and the presence of AN was stratified by World Bank income groups. Main food sources for micronutrients were also identified from 2 d of food records. Obesity and AN were measured by standardized staff. Results: Most USAP children did not meet daily intake recommendations for micronutrients, with low intake of calcium, potassium, vitamin D, vitamin E, excess sodium, vitamin A, folate, and niacin. Obesity was directly associated with thiamin intake and inversely associated with selenium intake. AN was inversely associated with calcium, copper, iron, phosphorus, potassium, riboflavin, vitamin B6, vitamin D, and vitamin E intakes and directly associated with selenium and pantothenic acid intake. Micronutrient intake imbalances were most associated with insulin resistance and obesity in lower-middle and high-income groups in the USAP region, respectively. Conclusions: The profile of micronutrient intake in USAP children and its association with obesity and insulin resistance can be used to provide precision nutrition policy guidance according to the World Bank income group to improve micronutrient intake and curb childhood obesity.